Numerical problems in physics Vol 2 - Pandey, Shashi Kant; Singh. Devraj (New Delhi Narosa Publishing House, 2016)
Mechanics, thermal physics, circuit fundamentals, electronics and spectroscopy
Keywords: thermal; spectroscopy; problems; Mechanics; fundamentals; electronics; circuit; 2